EFFECTS OF LEARNERS’ LANGUAGE PROFICIENCY ON THEIR LANGUAGE LEARNING STRATEGIES - Ho, Ai Ping; Ng, Lee Luan (Malaysian Association of Modern Languages, 2017)
Language proficiency is one prominent factor that could affect the use of language learning strategies (LLSs) in learning English as a second language among the learners. The influence of language proficiency on the use of LLSs might differ as language learning has extended to the contexts of learning other than the learners’ differences. With that in view, this study seeks to examine various types of LLSs based on the language proficiency of 1699 learners in a Malaysia tertiary context. This study utilised the adapted version of Strategy Inventory for Language Learning (SILL, 1990) Findings revealed that high proficiency learners employed LLSs from high to medium level whereas average and low learners showed medium strategy use of all LLSs. One-way ANOVA tests further indicated that there were significant differences in the use of direct strategies based on their language proficiency. It was also found that language proficiency had a significant influence on the use of cognitive, compensation, social, metacognitive and affective strategies. Positive to mix variation of the high strategy use for individual items of SILL with significant differences were reported. Implications of this study were also discussed.